The impact of first-trimester subchorionic hematomas on pregnancy outcomes after euploid embryo transfer: a retrospective cohort study - Weilin Wang; Qing Zhao; Yingbo Liu; Ling Guo; Wei Zhou; Qian Zhang; Junhao Yan; Tianxiang Ni (BMC, 2024)
Abstract Background The aim of the retrospective cohort study was to investigate the prognostic effect of subchorionic hematomas (SCH) in the first trimester on pregnancy outcomes after euploid embryo transfer. Methods We retrospectively analyzed women achieving singleton pregnancy by PGT-A or PGT-SR from January 2017 to January 2022. Patients were enrolled in the study if they had a viable intrauterine pregnancy at ultrasound between 6 0/7 and 8 0/7 weeks of gestation. Pregnancy outcomes as well as the incidence of maternal complications were compared between patients with and without SCH. Logistic regression was used for adjusting for potential confounding factors. Results A total of 1539 women were included, of which 298 with SCH and 1241 with non-SCH. The early miscarriage rate in SCH group was significantly higher than that in the non-SCH group (10.1% vs. 5.6%, adjusted odds ratio [aOR] 1.99, 95% confidence interval [CI] 1.25-3.16, P = 0.003). The live birth rate in SCH group was significantly lower than that in the non-SCH group. (85.6% vs. 91.2%, aOR 0.57, 95% CI 0.39-0.84, P = 0.005). In addition, SCH group had an increased risk of hypertensive disorder of pregnancy (HDP) (8.9% vs. 5.2%, P = 0.022), especially in hematoma with bleeding (19.3% vs. 6.0%, P = 0.002). The incidence of gestational diabetes mellitus (GDM), major congenital abnormalities rate, normal birth weight rate and low birth weight rate were similar between the two groups. Conclusions The presence of SCH in the first trimester was associated with worse pregnancy outcomes after euploid embryo transfer, including an increased risk of early miscarriage and hypertensive disorder of pregnancy, along with a reduced live birth rate.